A Study of the Effectiveness of the Expository Teaching Model in Relation to Student’s Personality (Review of Knowledge Economy, 2015)
The present study was carried out to compare the effects of Expository Teaching in English criterion test performance of Extrovert and Introvert type of students. Eighty (80) students from 12th class of higher secondary school & college students of Jammu District were taken consideration. The present study was modeled on single group pre-test, post-test experimental design. For statistical treatment of data, t-test was used for ascertaining the effects of extroversion and introversion on performance as measured through criterion-test. The results of our study with respect to main variable of personality show that extrovert and introvert group of students seem to be equally benefitted from the teaching in English through expository teaching model at 0.01 level of significance, whereas it is significant at 0.05 levels.